2017
DOI: 10.1049/iet-map.2016.0067
|View full text |Cite
|
Sign up to set email alerts
|

Coupled‐line directional coupler with tunable power division ratio and operating frequency

Abstract: This study presents a novel planar coupled‐line directional coupler with tunable both power division ratio and operating frequency, which is achieved using microstrip technology for the first time. Its tunability of the operating frequency and the power division ratio, or coupling ratio, can be independently controlled by the bias voltages. Moreover, it can simultaneously maintain perfect port match and isolation. On the basis of the even–odd mode analysis method, both the closed‐form analytical equations and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…The relative bandwidths under the criterions of return loss >20 dB, isolation >20 dB and amplitude imbalance <1 dB are also listed in Table 2. It can be found that the bandwidth of return loss >20 dB for the couplers in [14][15][16][17][18][19][20] are more than 2, 9, 10, 3.8, 9, 3, and 8%, respectively. While the bandwidth for the proposed coupler is more than 14.3%.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The relative bandwidths under the criterions of return loss >20 dB, isolation >20 dB and amplitude imbalance <1 dB are also listed in Table 2. It can be found that the bandwidth of return loss >20 dB for the couplers in [14][15][16][17][18][19][20] are more than 2, 9, 10, 3.8, 9, 3, and 8%, respectively. While the bandwidth for the proposed coupler is more than 14.3%.…”
Section: Resultsmentioning
confidence: 99%
“…While the bandwidth for the proposed coupler is more than 14.3%. The bandwidth of isolation >20 dB for the couplers in [15][16][17][18][19][20] are more than 22.5, 7.5, 1.1, 9, 4, and 10% respectively. While the bandwidth for the proposed coupler is more than 10.6%.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations